Efektivitas Program Lumbung Pangan dalam Upaya Mewujudkan Ketahanan Pangan di Kota Pekanbaru - Adinda Lestari; Nur Laila Meilani (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The effectiveness of the food granary program implemented by the Food Security Office of the city of Pekanbaru in implementing the Regulation of the Minister of Agriculture of the Republic of Indonesia Number: 17/Permetan/Hk.140/4/2015 is seen from indicators of program target accuracy, program socialization, achievement of program objectives and program monitoring. The purpose of this study is to analyze how the effectiveness of the food granary program in an effort to realize food security in the city of Pekanbaru using Budiani's theory, as well as analyze what are the inhibiting factors of the effectiveness of the food granary program in an effort to realize food security in the city of Pekanbaru. The method used in this study is qualitative research with a descriptive analysis approach that describes the effectiveness of the food granary program in an effort to realize food security in the city of Pekanbaru. In addition, to analyze the inhibiting factors of the effectiveness of the food granary program in efforts to realize food security in the city of Pekanbaru. The results of this study show that in the implementation of the food granary program, the food granary program plan that has been determined is not effective to be implemented. Inhibiting factors for the ineffectiveness of the program are the conversion of food barns that are used as residences by farmers making the crops produced by farmer groups directly sold to agents, maintenance of livestock that is not running well due to environmental factors, the existence of a land distribution system to farmer groups and the Agency.